Communication campaign on responsible consumption of fashion industry products: perception of the message and influence on the behavior of millennials in Colombia - Palacios-Chavarro, Janneth Arley (2023)
In recent years, the fashion industry has been identified as one of the major causes of environmental deterioration, including pollution, use of non-renewable resources, and waste generation, as well as the impact on other ecosystems. In this context, pro-environmental communication regarding responsible consumption is relevant, even though its study is an emerging field that offers new perspectives for analysis, particularly in terms of its contribution to the problem due to its influence on human behavior. Recent studies have shown that the millennial generation, or "millennials," who were born between 1981 and 2000, have caused significant changes in consumption habits. This paper presents the results of an analysis of the perception of communication campaigns' messages and their influence on responsible consumption of fashion industry products among millennials. To achieve this, a quantitative, descriptive, and associative study was designed based on 399 structured surveys administered to men and women between the ages of 20 and 31 in Colombia. The findings show significant relationships between opinions towards the messages and the gender variable, as well as a greater indifference (21.67%) among this population in the older age ranges (28 to 31 years old). It was also found that millennial women are more receptive to pro-environmental message of campaigns than men.